An interactive multi-objective linear programming approach for watershed planning-a case study - MOHANTY, R. R.; PAUL, J. C.; PANIGRAHI, B. (Journal of Soil and Water Conservation, 2022)
A watershed management planning study is carried out with the help of multi-objective programming approach and analysed with interactive technique (STEP method). The selected watershed is Mandakini Balinala watershed No-1 in Begunia block of Khurda district, Odisha. The total geographical area of the watershed is 506.67 ha, out of which the area treatable is 457 ha. The land allocation plan is done considering the major crops grown in the area i.e. paddy, maize, pigeonpea, mustard and green gram along with one fodder and fuel wood crop i.e. hybrid napier bajra and subabool. In the multi-objective approach, a compromise solution is obtained from the optimal solutions by the preference of Decision Maker (planner) by using interactive step method. The objective function taken for the maximisation are food, fodder, fuel wood, net income, labour employment generation and runoff water augmentation considering constraints of land, water and human resources. From the proposed plan the benefit-cost ratio was found to be 1.33:1 and the cropping intensity and the cropping intensity was found to be 163.37% (Kharif 85.83% and Rabi 77.54%). The benefit for the proposed planning is s 34782.59 Ã— 103 as compared to s 12234.25 Ã— 103 for the existing practice, which is 184% higher than the existing one.